Classroom Cleaning Duty to Cultivate Social Spirit and Responsibility at MTs Negeri 1 Yogyakarta - Iqbal, Muh; Alam, Lukis (Early Publishing, 2024)
Awareness of caring for the environment, especially for classroom cleanliness, is still a common problem in the school environment. The purpose of this study was to determine the character of the social soul and responsibility of students through class cleanliness pickets at MTs Negeri 1 Yogyakarta. This research method uses descriptive-qualitative with field research types. The data collection techniques use observation, structured interviews, and documentation. Then the data obtained were analyzed by reducing data, presenting data, and drawing conclusions. The results of this study indicate that class cleanliness picket activities at MTs Negeri 1 Yogyakarta can foster moral character values in students. These character values are such as a high social soul and responsibility. In addition, attitudes of discipline, cooperation, independence, and collaboration between students are also embedded in class cleanliness picket activities. So that class cleanliness pickets become something important for the lives of students in the future. This can happen because instilling student character is not only an activity that is routinely carried out every day but is able to build a more complex character of students, especially in the character of the social soul and responsibility of students.